2023
DOI: 10.3390/ijms24044122
|View full text |Cite
|
Sign up to set email alerts
|

Application of Gold Nanoparticles as Radiosensitizer for Metastatic Prostate Cancer Cell Lines

Abstract: More than 50% of all prostate cancer (PCa) patients are treated by radiotherapy (RT). Radioresistance and cancer recurrence are two consequences of the therapy and are related to dose heterogeneity and non-selectivity between normal and tumoral cells. Gold nanoparticles (AuNPs) could be used as potential radiosensitizers to overcome these therapeutic limitations of RT. This study assessed the biological interaction of different morphologies of AuNPs with ionizing radiation (IR) in PCa cells. To achieve that ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…AuNPr-PEG synthesis and functionalization were previously described and characterized by Soares, et al, 2022 [ 22 ]. The human metastatic cell lines from PCa were pre-treated for 24 h with 0.01 mM of AuNPr-PEG and submitted to a clinical radiation plan, daily fractionated ionizing radiation (2.5 Gy dose of ionizing radiation per day) over three days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AuNPr-PEG synthesis and functionalization were previously described and characterized by Soares, et al, 2022 [ 22 ]. The human metastatic cell lines from PCa were pre-treated for 24 h with 0.01 mM of AuNPr-PEG and submitted to a clinical radiation plan, daily fractionated ionizing radiation (2.5 Gy dose of ionizing radiation per day) over three days.…”
Section: Resultsmentioning
confidence: 99%
“…Their ability to selectively accumulate in tumor cells while sparing non-tumor cells improves the therapeutic outcome of radiation therapy. AuNPs, available in several shapes such as spheres, rods, stars, shells, and cages, offer a diverse spectrum of properties that influence their effectiveness as radiosensitizers in cancer therapy [ 22 , 23 ]. The distinct shapes of these nanoparticles play a crucial role in their interaction with radiation and cellular components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AuNPs offer diverse potential applications across various domains. Several in vitro studies demonstrated the anticancer potential of AuNPs as an anti-cancer agent as well as their stability, low toxicity, and specificity to PCa cells [6]. The traditional synthesis of AuNPs is highly polluting, wastes high levels of resources and energy, and nanoparticles can be toxic to the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation in the mechanisms governing the production and activation of inflammatory cells contributes to abnormal damage within the prostate tissue. Furthermore, the prostate tumour microenvironment hosts highly heterogeneous and plastic cell populations, which leads to patient resistance to therapies and heightened disease recurrence [6]. PCa cells reduction of PCa mortality following PSA screening.…”
Section: Introductionmentioning
confidence: 99%